(untitled) (Bangladesh Journal of Infectious Diseases, 2023)
Background: Surgical site infection (SSI) is one of the common causes of hospital borne infections. Objective: This study was performed to find out the proportion of multidrug resistant bacteria causing SSI. Methodology: This cross-sectional study was conducted among 99 hospitalized cases in the Department of Microbiology at, Bangladesh University of Health Sciences, Dhaka from July 2016 to June 2017. Ninety-nine bacteria were isolated from Pus samples collected aseptically from infected wounds from patients of BIHS general hospital. Isolation, identification and antibiotic sensitivity was done as per standard method. Results: Among the 99 organisms isolated, Gram negative bacteria were predominant (70.7%) than gram positive bacteria (29.3%). Among Gram positive bacteria (n=29), 31.0% were methicillin resistant. Among Gram negative bacteria (n=70), 7.1% isolates were ESBL, 78.6% AmpC β-lactamase and 12.3% were Carbapenemase producer. Higher generation antimicrobial agents like Meropenem and Imipenem are still effective against most of the organisms except carbapenemase producing ones. All Gram negative bacilli isolated were sensitive to colistin except Proteus species. Conclusion: In conclusion most of the isolates were multiply resistant to commonly prescribed antimicrobial agents. Bangladesh Journal of Infectious Diseases, December 2022;9(2):69-75